Upgraded Silicon Nanowires by Metal‐Assisted Etching of Metallurgical Silicon: A New Route to Nanostructured Solar‐Grade Silicon. (2nd May 2013) - Li, Xiaopeng; Xiao, Yanjun; Bang, Jin Ho; Lausch, Dominik; Meyer, Sylke; Miclea, Paul‐Tiberiu; Jung, Jin‐Young; Schweizer, Stefan L.; Lee, Jung‐Ho; Wehrspohn, Ralf B.
<x xml:space="preserve">Abstract</x> Through metal‐assisted chemical etching (MaCE), superior purification of dirty Si is observed, from 99.74 to 99.9884% for metallurgical Si and from 99.999772 to 99.999899% for upgraded metallurgical Si. In addition, large area of silicon nanowires (SiNW) are fabricated. The purification effect induces a ∼35% increase in photocurrent for SiNW based photoelectrochemical cell. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>